Discovery of Unexpected Sphingolipids in Almonds and Pistachios with an Innovative Use of Triple Quadrupole Tandem Mass Spectrometry - Federico Maria Rubino; Michele Dei Cas; Monica Bignotto; Riccardo Ghidoni; Marcello Iriti; Rita Paroni (Foods, 2020)
The densely packed storage of valuable nutrients (carbohydrates, lipids, proteins, micronutrients) in the endosperm of nuts and seeds makes the study of their complex composition a topic of great importance. Ceramides in the total lipid extract of some ground almonds and pistachios were searched with a systematic innovative discovery precursor ion scan in a triple quadrupole tandem mass spectrometry, where iso-energetic collision activated dissociation was performed. Five descriptors were used to search components with different C18 long chain bases containing different structural motifs (d18:0, d18:1, d18:2, t18:0, t18:1). The presence of hexoside unit was screened with a specific neutral loss experiment under iso-energetic collision activated dissociation conditions. The discovery scans highlighted the presence of two specific hexosyl-ceramides with a modified sphingosine component (d18:2) and C16:0 or C16:0 hydroxy-fatty acids. The hexosyl-ceramide with the non-hydroxylated fatty acid seemed specific of pistachios and was undetected in almonds. The fast and comprehensive mass spectrometric method used here can be useful to screen lipid extracts of several more seeds of nutraceutical interest, searching for unusual and/or specific sphingosides with chemically decorated long chain bases.